Implementation of the principles of legal certainty and legal justice in free decisions defendant of narcotics crime (Study decision number 281/Pid. Sus/2021/Pn Rni) - Ajlin, Ajlin; Kuswardani, Kuswardani; Ikhsan, Muchamad (The International Journal of Politics and Sociology Research, 2023)
The research aims to find out the legal basis and judge's considerations in the decision (Number 281/Pid. Sus/2021/PN RNI and to find out whether the decision (Number 281/Pid. Sus/2021/PN RNI) has fulfilled the principles of legal certainty and legal justice The research approach uses normative law, which is legal research by looking at library materials consisting of primary legal materials, secondary legal materials and tertiary legal materials. Then these legal materials will be processed and arranged systematically, studied, then conclusions will be drawn. related to the problem under study. Results: First, the legal facts show that the defendant was caught red-handed while taking a package containing leaves, stems and dried seeds, which is marijuana which is included in Class I narcotics at the JNE agent and the arrest was considered legal according to statutory regulations. in force, as stated in the decision of the Raba Bima District Court Number 281/Pid. Sus/2021/PN RNI, the defendant was not proven to have violated the provisions of Article 114 paragraph (1) of Law Number 35 of 2009 on Narcotics Crimes and the defendant was acquitted, after carrying out basic legal analysis and careful consideration, the defendant's mistake was proven to fulfill the elements of possession of the goods. However, in this case the judge did not carefully interpret the element of control so that the decision was considered wrong both theoretically and practically.